Tuning the optoelectronic properties of oligothiophenes for solar cell applications by varying the number of cyano and fluoro substituents for solar cell applications: A theoretical study - Franco, Francisco C., Jr. (Animo Repository, 2020)
Chemical modifications through substitution are observed to be effective in controlling the optoelectronic properties of various polymers for different applications. In this study, density functional theory–based calculations are employed to investigate the optoelectronic properties of several oligothiophenes based on poly(3-hexylthiophene-2,5-diyl) by varying the number of fluoro and cyano substituents attached. The resulting structures of the polymer derivatives are affected by the electrostatic interactions between the cyano or fluoro groups and the adjacent thiophene unit. Of the two, cyano substitution results in much lower frontier orbital energies for the same number of substituents. It was observed that a decrease in the highest occupied molecule orbital and lowest unoccupied molecular orbital energies correlates very strongly with the number of cyano and fluoro substituents. The effect of the cyano and fluoro groups on the frontier orbitals is also demonstrated and observed to correlate strongly with a lowering of the highest occupied molecule orbital and lowest unoccupied molecular orbital energies as the number of substituents is varied. The predicted solar cell characteristics reveal that most cyano and fluoro derivatives will have improved characteristics compared to unsubstituted poly(3-hexylthiophene-2,5-diyl). This theoretical study shows that by varying the number of electron-withdrawing substituents, the optoelectronic properties may be tuned for solar cell applications. © The Author(s) 2019.